Global research trends of steroid-induced osteonecrosis of the femoral head: A 30-year bibliometric analysis - Lu, Chao; Qi, Haodong; Xu, Hanbo; Hao, Yangquan; Yang, Zhi; Yu, Wenxing; Xu, Peng (Frontiers in Endocrinology, 2022)
Objective: To explore the global research trends and hotspots of steroid-induced osteonecrosis of the femoral head (SONFH) through qualitative and quantitative analysis of bibliometrics. Methods: All publications on SONFH published from 1992 to 2021 were extracted from the Web of Science Core Collection database. CiteSpace was used for the visualization analysis of major countries, active institutions, productive authors, and the burst of keywords. VOSviewer was used for coupling analysis of countries/regions, institutions, and authors. Microsoft Excel 2017 was used for statistical analysis, drawing bar charts, pie charts, and cumulative area charts. The software of MapInfo was used to draw the distribution map of the publications. Results: A total of 780 publications were included for analyses. The most productive year was 2020 with 98 records. China was the most influential country with 494 publications, an H-index of 59, and total citations of 16820. The most prolific institution was Shanghai Jiaotong University in China with 53 publications and 998 citations. Clinical Orthopaedics and Related Research (IF = 4.755, 2021) was the most active journal with 26 articles. The hot keywords were “osteonecrosis”, “avascular necrosis”, “osteogenic differentiation”, “proliferation”, “PPAR gamma”, “apoptosis”, “oxidative stress”, “genetic polymorphism” and “mesenchymal stem cells”. The keywords like “proliferation”, “PPAR gamma” and “genome-wide” have emerged in recent years. Conclusion: The number of publications in SONFH has increased significantly in the last three decades. The pathologic mechanism of SONFH gathered most research interests. Genomics and cell molecular biology of SONFH are the research frontiers.